TITLE: INTERCULTURAL COMMUNICATION: A COMPARATIVE STUDY BETWEEN SLOVAK AND UZBEK CULTURES - Ozodakhon Uktamova Ilhomjon kizi (TADQIQOTLAR.UZ, 2024)
Abstract This study investigates the unique characteristics of intercultural communication between  Slovak  and  Uzbek  cultures,  with  a  focus  on  sociolinguistic  features  and cultural norms. Using qualitative methods, this research explores the direct and indirect communication styles, emotional expressivity, and politeness frameworks within each culture.  Findings  reveal  that  while  Slovak  communication  often  embodies  a  more individualistic, low-context approach, Uzbek communication aligns with collectivistic, high-context principles, impacting both verbal and non-verbal interactions. (Brown & Levinson, 1987) These insights provide practical implications for enhancing mutual understanding and effective communication in diverse settings.